The use of mnemonic formulas to quickly find the ration of lactating - Eyzaguirre, Rómulo (1918)
It is often daily, in private practice in child medicine, need fast tables that indicate the portions of the infant, but how are you have many terms, and all essentially numerical, it is almost impossible to keep in memory all the details of these tables. With good fortune, you can recall one or more of the statements of this or that month of the child's life, more in the moment - that the pilot did not choose, but the clinical case is offered - it is necessary formulate the conditions of feeding the baby, is the operator with a lack of tables, or infidelity of memory in the whole series of them, or statements of doubt that the case, worth as much as the complete oblivion well apart from the fact natural, not being able to remember all the numbers that are abundant table of rations.